(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
The purpose of the study is to examine the level of Strategic Information Use (SIU) among managers in Malaysia business organization. SIU among managers has raised a concern by many researchers in advanced countries as compared to Malaysia. The quantitative method of study and survey was conducted on 491 senior managers in manufacturing and financial services companies in Klang Valley, Malaysia. The findings indicate that the SIU level Malaysia business organization was high. It was also found that there was a significant difference between SIU in manufacturing and financial services companies. The result may provide further insights into SIU among managers in Malaysia business environment.